2013
DOI: 10.1002/ijc.28647
|View full text |Cite
|
Sign up to set email alerts
|

MED15, encoding a subunit of the mediator complex, is overexpressed at high frequency in castration‐resistant prostate cancer

Abstract: The mediator complex is an evolutionary conserved key regulator of transcription of protein-coding genes and an integrative hub for diverse signaling pathways. In this study, we investigated whether the mediator subunit MED15 is implicated in castration-resistant prostate cancer (CRPC). MED15 expression and copy number/rearrangement status were assessed by immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), respectively on 718 prostate cancer (PCa) specimens and sequenced by Sanger on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…Recently, we have found similar expression patterns in PCa tissues and functional results in cell lines for the Mediator tail subunit MED15 (Shaikhibrahim et al 2013). The interplay between different subunits of the Mediator complex provides the basis for the function of the Mediator as a hub between signaling pathways and the transcription of specific genes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Recently, we have found similar expression patterns in PCa tissues and functional results in cell lines for the Mediator tail subunit MED15 (Shaikhibrahim et al 2013). The interplay between different subunits of the Mediator complex provides the basis for the function of the Mediator as a hub between signaling pathways and the transcription of specific genes.…”
Section: Discussionmentioning
confidence: 60%
“…The response of metastatic PCa cell lines to TGFb depends on the cellular microenvironment. In a recent study, we observed increased proliferation of the PCa cell line PC3 in response to exogenous TGFb3 when cells were grown in the presence of all growth factors (Shaikhibrahim et al 2013). Other studies showed that TGFb treatment had no effect upon proliferation in PC3 cells when cells were plated in serum-free medium (Vo et al 2012).…”
Section: Introductionmentioning
confidence: 81%
“…Most evidence has been gathered for the kinase module subunit CDK8, which has been linked to colon and pancreatic cancer (8,9) and was also investigated as a potential target in cancer therapy (10,11). Other subunits have also been reported in neoplastic conditions such as MED12 in uterine leiomyomas, fibroepithelial breast tumors, and prostate cancer (12)(13)(14), MED15 in prostate cancer and head and neck cancer (15,16), and cyclin C in acute lymphoblastic leukemia (17). In addition, some subunits have been linked to altered hormone receptor signaling such as MED1 in breast cancer and prostate cancer (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…21 We recently reported the implication of MED15 in castration-resistant prostate cancer and its direct link to transforming growth factor (TGF)-b signaling in this disease. 22 Notably, TGF-b signaling is involved in HNSCC, 23 and a large study reported alterations in SMADdependent TGF-b signaling at high frequency and revealed that patients with active SMAD signaling exhibited worse survival rates. 24 Moreover, abnormalities in SMAD-interacting proteins have been described to contribute to dysregulated TGF-b signaling.…”
mentioning
confidence: 99%
“…24 Moreover, abnormalities in SMAD-interacting proteins have been described to contribute to dysregulated TGF-b signaling. 21,22,25 Therefore, we aimed to investigate whether MED15 is implicated in HNSCC and thus further contribute to the understanding of the molecular basis of this disease.…”
mentioning
confidence: 99%